A new sesquiterpene from the barks of Manglietia hookeri. Issue 21 (1st November 2016) - Bao, Yangmei; Wang, Wenshu; Wu, Haibo; Qi, Muge; Li, Jiajie; Yang, Yujie
Abstract: A new sesquiterpene manghookerins A (1 ) was isolated from the barks of Manglietia hookeri (Magnoliaceae) together with five known eudesmane-type sesquiterpenes. The structure of manghookerins A (1 ) was elucidated by physical and spectroscopic data analysis, including 1D and 2D NMR, HR-ESI-MS and X-ray diffraction. The structures of known sesquiterpenes were established by comparing their spectroscopic data with those in literatures. Abstract :